Fiscal policy of Germany's grant coalition 2015: A balanced budget at all cost? - Christoph Bierbrauer (ISM Research Journal, 2015)
According to the Bundesregierung (2014) and the medium-term projections issued by the Ger-man finance minister, Germany's federal budget will be balanced from 2015 onwards. This paper presents a discussion on the efforts undertaken by the German government to bal-ance its budget against the backdrop of related theoretical and empirical results. It evaluates alternative fiscal policy measures in an overlapping generations' structure of the Blanchard (1985) and Yaari (1965) type as suggested in Bierbrauer (2012). A major finding is that after decades of constant deficits such a feat is not achieved easily and comes mainly at the cost of reduced public investments in Germany. In the model, alternative measures to reduce fiscal deficits have very different effects on key macroeconomic variables. In general, austerity dampens the overall economic activity. Howev-er, the magnitude of these effects strongly depends on the chosen consolidation strategy. The German government relied on spending cuts, both in public consumption and investment. Based on the model simulation and the empirical evidence available, the latter is neither the most promising with regard to successful debt reduction in the medium and long term nor the least harmful with regard to the implied effects on the overall economic activity. The results suggest that the German government needs to adjust its strategy by focussing more on reducing public consumption and abandoning consolidation efforts that decrease the level of public in-vestment.
Keywords: 650